Next generation assessment : moving beyond the bubble test to support 21st century learning - Darling-Hammond, Linda, 1951-; Abedi, Jamal (San Francisco, CA : Jossey-Bass, a Wiley brand, 2014)
'Next Generation Assessment examines performance assessment as an alternative to the current high-stakes standardized testing system. This important resource provides a thorough analysis of the prospects and challenges of sustaining performance assessments on a large scale. Linda Darling-Hammond, with a team of leading scholars, describes the history and current uses of performance assessments in the United States and abroad and summarizes the latest findings in the field.The experts determine that large-scale testing in the United States may be dramatically improved by the thoughtful incorporation of well-constructed performance assessments that can represent higher-order, cognitively demanding standards. This summary volume to Beyond the Bubble Test is designed for the busy practitioner--and all who are interested in how schools can successfully supplement traditional tests with something that works better. Next Generation Assessment offers an accurate evaluation of the benefits and possibilities for adopting better performance assessments nationally.PRAISE FOR NEXT GENERATION ASSESSMENT'Pointing to current policies and practice, this book is an excellent guide directing educators on how to transition to an assessment system that genuinely shapes, informs, and improves learning for all students and teachers.'--Governor Bob Wise, president, Alliance for Excellent Education; author of Raising the Grade'This book helps us to think strategically about accountability and assessment in our public schools and to understand how performance-based approaches--instead of rote memorization--can allow schools to support both deeper learning and higher standards.'--Randi Weingarten, president, American Federation of Teachers'--
Machine generated contents note: Acknowledgments vi The Authors vii 1 Beyond the Bubble Test: How Performance Assessment Can Support Deeper Learning 1 2 Defining Performance Assessment 15 3 Experiences with Performance Assessment in the United States and Abroad 31 4 How Performance Assessment Can Support Student and Teacher Learning 43 5 Meeting the Challenges of Performance Assessments 57 6 Making High-Quality Assessment Affordable 75 7 Building Systems of Assessment 87 8 Conclusion 107 Notes 113 Index 125 .
Includes bibliographical references and index.
Keywords: Educational tests and measurements